DIGITALIZING FORMATIVE ASSESSMENT QUESTIONS BANK WITH QUIZZIZ - Tedi Rohadi; Shofia Mardhiyah (Universitas Widyatama, 2023)
Some teachers have always been encountering difficulties in writing an assessment especially a formative assessment. It is apparent that assessment is necessary to measure the achievement of learning objectives in teaching and learning to meet today's needs. This study aims to scrutinize the current books of question bank products as a benchmarking and attempt later on to design a preliminary digitalized question bank form to help teachers conduct formative assessments. The study uses research and development model and qualitative approach. It applied three phases of Borg & Gall's theory: research and information gathering, planning, and preliminary product development. Documentary data collection techniques are used to identify the characteristics and limitations of the question bank. A critical literature review and qualitative item analysis were used to analyse the data. Twenty-six question bank indicators were identified from a review of related literature. Twenty-six indicators are used to investigate weaknesses in current question bank products. Ten shortcomings were identified in both products meanwhile the second product has fewer defects than the first. The preliminary form of the digitalized question bank was designed by adapting existing products and overcoming their shortcomings. Forty entries were written and displayed in a test. The developed items are characterized to be more relevant to higher-level thinking which is analysis level cognitive domain about 48%. In addition 52.5% of the developed items are identified as medium difficulty.